Current trends and latest developments in echocardiographic assessment of right ventricular function: load dependency perspective - Nonaka, Hideaki; Rätsep, Indrek; Obonyo, Nchafatso G.; Suen, Jacky Y.; Fraser, John F.; Chan, Jonathan (Frontiers in Cardiovascular Medicine, 2024)
Right ventricle (RV) failure is a common complication of many cardiopulmonary diseases. Since it has a significant adverse impact on prognosis, precise determination of RV function is crucial to guide clinical management. However, accurate assessment of RV function remains challenging owing to the difficulties in acquiring its intricate pathophysiology and imaging its complex anatomical structure. In addition, there is historical attention focused exclusively on the left ventricle assessment, which has led to overshadowing and delayed development of RV evaluation. Echocardiography is the first-line and non-invasive bedside clinical tool for assessing RV function. Tricuspid annular plane systolic excursion (TAPSE), RV systolic tissue Doppler velocity of the tricuspid annulus (RV S'), and RV fractional area change (RV FAC) are conventional standard indices routinely used for RV function assessment, but accuracy has been subject to several limitations, such as load-dependency, angle-dependency, and localized regional assessment. Particularly, load dependency is a vexing issue, as the failing RV is always in a complex loading condition, which alters the values of echocardiographic parameters and confuses clinicians. Recently, novel echocardiographic methods for improved RV assessment have been developed. Specifically, “strain”, “RV-pulmonary arterial (PA) coupling”, and “RV myocardial work” are newly applied methods for RV function assessment, a few of which are designed to surmount the load dependency by taking into account the afterload on RV. In this narrative review, we summarize the latest data on these novel RV echocardiographic parameters and highlight their strengths and limitations. Since load independency is one of the primary advantages of these, we particularly emphasize this aspect.